Entrepreneurial culture in small businesses in Sinaloa - Cárdenas, Alberto Rodríguez; López, Esteban Otoniel Moreno; López, Adrián Cuevas; Berrelleza, Aldo Alán Cuadras; Martínez, Senén Reyes; Parra, Alfonso Reyna; López, José de Jesús López (Technium Social Sciences Journal, 2024)
This research work aimed to analyse the conditions of entrepreneurial activity and culture in the environment of small businesses in Sinaloa, considering the relevance and correlation between success stories and their processes. The importance of this topic is that there is a requirement for administrative orientation since the functions of the partners are related to the administrative role, and they have been updating themselves in the processes and management of local and international transactions that mark the new orientations. In this way, innovative techniques and strategies are required to deal with conflicts in relation to the above. Likewise, this will enable them to develop and implement strategies and actions aligned with the technological and sustainable (social, economic, and environmental) advances that are demanded today in the rules of world trade. Hypothesis. Adequate management is considered a pillar for the long-term success of small businesses, motivating the innovative spirit of an organisation's partners, and creating competitive advantages for the organisation over its competitors.